2002
DOI: 10.4141/s01-049
|View full text |Cite
|
Sign up to set email alerts
|

Longevity of deep ripping effects on Solonetzic and associated soils

Abstract: Mathison, M. N., Chanasyk, D. S. and Naeth, M. A. 2002. Longevity of deep ripping effects on Solonetzic and associated soils. Can. J. Soil Sci. 82: 259-264. The longevity of deep ripping effects on Solonetzic soils was investigated at 11 field sites in eastcentral Alberta after a period of 15 to 20 yr. Select soil properties and crop yield of deep-ripped and non-ripped control plots were analyzed. Dryland yield data of wheat, barley, oats and canola were assessed for 10 of the 11 sites over a 16-yr time period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Chanasyk continued the deep plowing research in the 1990s (Travis et al 1991). He led investigations into effects of deep ripping and organic matter amendments on reclaimed coal mine soils (Bateman 1992;Bateman andChanasyk 1992a, 1992b;Harrison et al 1992), and longevity of deep ripping and subsoiling effects on Solonetzic soils on agricultural lands (Goddard and Chanasyk 1990;Watson and Chanasyk 1992;Mathison 2000).…”
Section: Salinity and Acidificationmentioning
confidence: 99%
“…Chanasyk continued the deep plowing research in the 1990s (Travis et al 1991). He led investigations into effects of deep ripping and organic matter amendments on reclaimed coal mine soils (Bateman 1992;Bateman andChanasyk 1992a, 1992b;Harrison et al 1992), and longevity of deep ripping and subsoiling effects on Solonetzic soils on agricultural lands (Goddard and Chanasyk 1990;Watson and Chanasyk 1992;Mathison 2000).…”
Section: Salinity and Acidificationmentioning
confidence: 99%
“…Many areas in northeastern BC are characterized by clay-rich soils (Lord and Green 1986), and limited information is available about how these soils will respond (i.e., puddling versus persistence of introduced structure) subsequent to tillage (Bulmer 1998). Mathison et al (2002) demonstrated that even more than 15 years following treatment, penetration resistance was significantly lower in deep ripped soils, despite a lack in significantly different bulk densities between soils.…”
mentioning
confidence: 96%
“…Where Solonetzic soils are concerned, increased clay content in the A horizon along with an increase in elements such as sodium may result from tillage and can affect soil productivity (Mathison et al 2002).…”
mentioning
confidence: 99%